2021
DOI: 10.3389/fneur.2021.769216
|View full text |Cite
|
Sign up to set email alerts
|

Tap Test Can Predict Cognitive Improvement in Patients With iNPH—Results From the Multicenter Prospective Studies SINPHONI-1 and –2

Abstract: Background: We analyzed the predictive value of the tap test (TT) on the outcome of cerebrospinal fluid (CSF) shunting in patients with idiopathic normal pressure hydrocephalus (iNPH) and cognitive impairment up to 12 months postoperatively.Methods: We analyzed the data of two prospective multicenter studies on ventriculoperitoneal shunt (VPS) and lumboperitoneal shunt (LPS) use in iNPH patients. We selected patients with Mini-Mental State Examination (MMSE) scores ≤ 26 points as study subjects. We used a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
2
Order By: Relevance
“…However, contrary to our results, Nakajima et al (2021) reported that postoperative improvement in MMSE scores was predictable based on MMSE score changes after CSF tapping. Likewise, Kazui et al (2013) reported that baseline MMSE scores were significantly associated with postoperative MMSE improvement.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, contrary to our results, Nakajima et al (2021) reported that postoperative improvement in MMSE scores was predictable based on MMSE score changes after CSF tapping. Likewise, Kazui et al (2013) reported that baseline MMSE scores were significantly associated with postoperative MMSE improvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Postoperative MMSE was performed 12 months after surgery in the two studies; in our study, the average number of days from surgery to postoperative MMSE was 42. Furthermore, in Nakajima and colleagues’ (2021) study, the period from CSF tapping to the MMSE was 1 week, whereas in ours, it was 24–48 hours. Another study on longitudinal change after CSF tapping showed that MMSE scores recovered more slowly than FAB scores (Matsuoka et al, 2018).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Based on the criterion of at least 10% improvement in gait velocity in the timed up and go evaluation 15 , 70% (low-DESH group) and 62.5% (high-DESH group) patients showed improvement, respectively. Improvements of 3 or more points in cognitive function assessed by Mini-Mental State Examination (MMSE) before and after the CSF tap test were observed in approximately 20 and 18.8%, respectively 16 . Shunt surgery was performed in only 8 of 33 patients, all but one of whom were in the high-DESH group.…”
Section: Resultsmentioning
confidence: 99%
“…A responder was defined as a patient who showed an improvement of 10% or more in walking speed 6 h and 24 h after the CSF tap test, based on the results of the timed up and go evaluation performed at the time of the tap test 15 . For cognitive function, we checked the change in MMSE score before and after the CSF tap test to determine if the score improved by 3 points or more 16 . We investigated whether a ventriculoperitoneal shunt operation was performed and checked the change in symptoms before and after the operation through the electronic medical records.…”
Section: Methodsmentioning
confidence: 99%